2017
DOI: 10.1089/cbr.2017.2249
|View full text |Cite
|
Sign up to set email alerts
|

Current Targeted Therapies in HER2-Positive Gastric Adenocarcinoma

Abstract: Gastric cancer is one of the most common types of cancer in the world, usually diagnosed at an advanced stage. Despite the advances in specific anticancer agents' development, the survival rates remain modest, even in early stages. In 15%-20% of cases, the human epidermal growth factor receptor 2 (HER2) overexpression was identified. We conducted a general review to summarize the progress that has been made in the targeted treatment of HER2-positive esogastric junction or gastric adenocarcinoma. According to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 122 publications
1
14
0
Order By: Relevance
“…The preferred regimen for second-line treatment is ramucirumab plus paclitaxel, or ramucirumab monotherapy if the patient is not eligible for paclitaxel (Table S2 in Supplement) [3, 10, 56–58]. A PD-1 inhibitor has recently been approved as third-line or higher therapy for GC/GEJC patients in the US [61].…”
Section: Resultsmentioning
confidence: 99%
“…The preferred regimen for second-line treatment is ramucirumab plus paclitaxel, or ramucirumab monotherapy if the patient is not eligible for paclitaxel (Table S2 in Supplement) [3, 10, 56–58]. A PD-1 inhibitor has recently been approved as third-line or higher therapy for GC/GEJC patients in the US [61].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical practice, the treatment of gastric and gastroesophageal adenocarcinoma with Lapatinib alone seems to be more challenging compared to its application in breast cancer. Particularly, it seems that it is only suitable for a subset of patients [ 31 , 32 ]. We tested whether Her2 status itself may already influence autophagy under basal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab and nivolumab are an anti-PD1 monoclonal antibody, and they facilitated the capacity of the immune system. A phase II study (KEYNOTE-059) demonstrated that application of pembrolizumab alone showed clinical efficacy in previously treated advanced GC[ 66 ]. Treatment of pembrolizumab showed a higher overall response rate (ORR) for patients with PD-L1 positive tumors, than in patients with PD-L1 negative tumors.…”
Section: Current Topics Of Biomarkers In Gcmentioning
confidence: 99%